Prenatal diagnosis of congenital high airway obstruction syndrome: our experience from a tertiary care center - Saxena, Deepti; Phadke, Shubha R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Congenital high airway obstruction syndrome (CHAOS) is an extremely rare and life-threatening condition. It occurs due to obstruction in fetal respiratory tract and is characterized by typical ultrasonographic findings. Risk of recurrence is low, so antenatal diagnosis can help in counselling regarding risk of recurrence. A retrospective record review of all cases referred to our institution for antenatal ultrasound over a period of 5 years from January, 2014 to December, 2018 was done. Cases diagnosed as CHAOS were reviewed in detail regarding the radiological findings, information regarding delivery, fetal karyotype and postnatal/ fetal examination. Between the period of 2014 to 2018 three fetuses with CHAOS were identified. All of them had characteristic radiological features. Two of them were associated with hydrops and one fetus had oligohydramnios. All the pregnancies were terminated after antenatal diagnosis. Amniocentesis was done in 2 out of 3 cases and fetal karyotype was found to be normal. Fetal autopsy was done in one case and site of upper airway obstruction was identified. Confirmation of diagnosis by antenatal ultrasound and if possible, by post-mortem examination is essential for providing estimation of risk of recurrence to the family and genetic counselling.